Diversity and Abundance of Rhopalocera (Lepidoptera) in Batutegi Protected Forest, Sumatra, Indonesia - Cita Ramadhanti; Aris Subagio; Jani Master (Berkala Ilmiah Biologi, 2022)
Butterflies are diurnal animals, divided into six families which are Hesperiidae, Lycaenidae, Nymphalidae, Papilionidae, Pieridae, and Riodinidae. Butterflies can be found in any vegetation as long as their host and feed plants are available. Batutegi protected forest has the potential to be butterflies habitat due to the possibility of its richness of host and feed plants. The research was conducted to analyze butterflies diversity and abundance in three different types of vegetation which are shrubs, forest, and Way Sekampung watershed. The methods that used are Shannon-Wiener’s Diversity Index (H’), Simpson’s dominance index (D), and Pielou’s Evenness Index (E). Analysis shows the butterfly diversity up to 3.034; dominance index up to 0.079; and evenness up to 0.823. These results attributed to the highly potential of butterfly diversity, stable evenness, and low butterfly species dominance. Analysis of diversity index in three vegetation obtained result H’ = 3.034 shows that the butterfly community is stable. The evenness index showed a high value E = 0.823 means that the individual of each type is evenly distributed. The dominance index obtained a low value D = 0.079 indicates that no particular type dominates all vegetation.